Influence of Teachers’ Effective Teaching Behavior on Knowledge Transfer of Students in Online Teaching - Tan, Hongwei (International Journal of Emerging Technologies in Learning (iJET), 2022)
With the rapid development of information technology, the online education environment has become a reality. In specific online education practices, most teachers exhibit effective teaching behaviors by using multimedia technologies positively to stimulate the learning initiative of students, improve their learning performances, and promote their knowledge transfer. Based on theories of knowledge transfer and effective teaching behaviors, a measurement model that focuses on the effects of effective teaching behaviors of teachers on knowledge transfer of learners was constructed in this study. Moreover, the influencing mechanism of effective teaching behaviors of teachers (clear teaching, diversified teaching, task orientation, and guidance of student engagement) on knowledge transfer of students was discussed through questionnaire survey and multiple regression analysis. In addition, differences in knowledge transfer caused by different online learning platforms were analyzed. Results demonstrate that for the designed questionnaire, the general Cronbach’s α=0.796 and KMO values 0.820, indicating that the designed questionnaire has very good reliability and validity. Four aspects of clear teaching, diversified teaching, task orientation, and guidance of student engagement have significant positive correlations with knowledge transfer. Diversified teaching, task orientation, and guidance of student engagement can also promote knowledge transfer of students significantly. According to the Kruskal-Wallis test statistics, online learning platforms have significant effects on the knowledge transfer at the 0.05 level. Research conclusions have important references to recognize components of effective teaching behaviors of teachers, promote knowledge transfer improvement of students comprehensively, and facilitate the positive transformation of teachers to online teaching modes and strategies.